Sistem Pengontrol Pintu Otomatis Ruangan Fakultas Ilmu Komputer Berbasis IOT - irvan salihi (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2022)
Abstract: IoT (Internet of Things) is a technology concept that allows every device to be connected to the internet network. A security system, in general, is to secure an object where the object contains important things security matters such as a house, room, building, or other things. The problem, in general, is that today's doors still utilize conventional locks, which are still less secure because they are easy to break by thieves. The system development method used is a prototype model. The presentation of the hardware aspects to be built will appear to the user quickly. The prototype is evaluated by both parties so that the screening of hardware development needs can be quickly carried out to meet the wishes and needs. This study employs the NodeMcu ESP8266 microcontroller functioned as the main chip that controls all processes occurring. The input from this microcontroller comes from a smartphone that sends values to the NodeMcu ESP8266, which will later be processed. This system has the output of the process carried out by the NodeMcu ESP8266. It is by activating the relay to provide voltage to the solenoid, so the door can be opened and locked. This automatic door control system runs as expected. It is able to open or lock doors that are controlled remotely by the user by giving commands or conditions through the Google Assistant application.